Eye Motility - Mravicic, Ivana (IntechOpen, 2019)
Visual processing refers to the ability to perceive three-dimensional images. To accomplish this, our eyes have to be perfectly tuned and work together. Each eye perceives a slightly different image that the brain then has to unite into a single three-dimensional picture. This book explains the motor and sensory steps necessary for forming binocular and stereo vision, discusses tests to assess the different steps and describes disruptions that can occur in the eyes and the brain. Because of the sensitivity of the developing child's eye, the book also addresses the assessment of children's vision. This book will appeal to ophthalmologists, paediatricians, neurologists and other interested readers.